1993
DOI: 10.1111/j.1756-1051.1993.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

The intergeneric hybrid grass “Poa labradorica”

Abstract: The new nothogenus x Dupoa (Dupontia x Poa) is published. Nomenclature of the only known nothospecies, x Dupoa labradorica (= Poa labradorica), is discussed. Morphology and synecology of this poorly known arctic and subarctic grass are described and a key to related taxa is given. Its morphology and ecology overlap with the putative parental taxa, Poa eminens and Dupontia fisheri ssp. psilosantha. Establishment and persistence of this sterile hybrid are related primarily to geological processes associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The intergeneric hybrid genus ÂDupoa (=Dupontia  Poa) includes a well documented sterile clonal hybrid between Poa (subg. Arctopoa) eminens and D. fisheri that occurs in northern Quebec-Labrador (Cayouette and Darbyshire 1993). Although Dupontia itself is suspected to be of hybrid origin, neither Cayouette and Darbyshire (1993) nor Byrsting et al (2004) …”
Section: Reticulate Evolutionmentioning
confidence: 96%
“…The intergeneric hybrid genus ÂDupoa (=Dupontia  Poa) includes a well documented sterile clonal hybrid between Poa (subg. Arctopoa) eminens and D. fisheri that occurs in northern Quebec-Labrador (Cayouette and Darbyshire 1993). Although Dupontia itself is suspected to be of hybrid origin, neither Cayouette and Darbyshire (1993) nor Byrsting et al (2004) …”
Section: Reticulate Evolutionmentioning
confidence: 96%
“…& Darbysh. ; Cayouette & Darbyshire, 1993;. Using DNA sequence data Brysting et al (2004) showed that Dupontia together with Arctophila was sister to Arctagrostis, but phylogenetically isolated from Deschampsia s.s. or s.l.…”
Section: Chromosomes In Dadmentioning
confidence: 99%
“…In the work by Darbyshire & al. (1992) and Cayouette & Darbyshire (1993), Poa eminens and Dupontia fisheri were pointed out as parental species of the intergeneric hybrid ×Dupoa labradorica (Steudel) J. Cayouette & S. J. Darbyshire. This example represents an early stage of evolution of a hybrid in which the chances of detecting both parents are greater than at a later stage as might be the case in Dupontia.…”
Section: The Possible Intergeneric Hybrid Origin Ofmentioning
confidence: 99%